KISAH DUA TANAH PERDIKAN: PERUBAHAN STATUS WILAYAH BEBAS PAJAK DI KERAJAAN MATARAM ISLAM ABAD VIII DAN KERAJAAN SIAM ABAD XX - Hendri Gunawan; Muhammad Anggie Farizqi Prasadana (Handep: Jurnal Sejarah dan Budaya, 2022)
Perdikan land or tax-free land in Indonesia and Thailand is used for religious purposes. This study aims to determine the change in tax-exempt status in Indonesia and Thailand, especially in the Islamic Mataram Kingdom and Siam Kingdom. This research used historical methods consisting of topic selection, source collection, source criticism, interpretation, and writing. The result shows the existence of tax-free areas in Indonesia and Thailand has been going on for a long time. However, tax-free land in Indonesia was revoked after independence because it was considered injustice. Differently, tax-free land in Thailand still exists but no longer receives forced labor support from the king, replaced with wage labor because of the money economy influence that Chinese trader brought and for the abolition of slavery. In conclusion, tax-free lands in these two countries have different fates due to social and economic changes.